Analisis Pengendalian Persediaan Farmasi di Rumah Sakit Awal Bros Batam - Hilda Muliana; Ronny Sutanto; Sabda Wahab (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2022)
Prescription delays at Pharmacy Department services Awal Bros Batam Hospital during the month of October 2015 until September 2016 influences the impact on the quality of hospital services and going on back order ending with financial problems to Awal Bros Batam hospitals. The author wants to identify problems that occur for improving efficiency and effectiveness of services pharmacy inventory control at Awal Bros Batam Hospital and overall improving the quality of hospital services. This study is an operational research study to develop a pharmaceutical inventory control models. The first model, in this study will be made use of ABC analysis, investment analysis ABC, and ABC critical index, to determine pharmaceutical supplies into groups A, B and C. Furthermore, will be calculated EOQ and ROP, as well as the efficiency of TIC. Conducted in-depth interviews with informants. The second model, the method Periodic Review System, Order up to the level, in this study also conducted an analysis 10 largest inventory investment by ABC and ABC average user through the assessment of inventory, ITOR and PNP on Awal Bros Batam hospital over a period of 12 months. In the second method is expected to avoid overstocking pharmaceuticals with high investments that may affect the cash flow of the hospital. Pharmacy inventory control at Awal Bros Batam Hospital has not performed optimally, although every month have made the ABC analysis Investments and apply maximum and minimum stock method is simple. This research, produce policy recommendations for the Awal Bros Batam Hospital to help the management to improve ppharmacy inventory control and solve the problems in the pharmaceutical stock out.